2021
DOI: 10.1177/1759720x20986734
|View full text |Cite
|
Sign up to set email alerts
|

The role of ixekizumab in non-radiographic axial spondyloarthritis

Abstract: Among patients with axial spondyloarthritis (axSpA), non-radiographic axial spondyloarthritis (nr-axSpA) is distinguished from ankylosing spondylitis (AS) by a lack of obvious radiographic changes in the sacroiliac joint. Tumor necrosis factor inhibitor (TNFi) has been used as a highly effective treatment in patients with AS and has shown good efficacy and safety in clinical trials in patients with nr-axSpA. As the pathophysiological mechanism for axSpA has started to become better recognized, various drugs ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“… 23 At present, there are two anti-IL-17A biologics approved for the treatment of axSpA: secukinumab and ixekizumab. 24 Further anti-IL-17 biologics, such as brodalumab and bimekizumab, are being evaluated in clinical trials in patients with axSpA; these therapies, however, are still in clinical development and are not currently indicated in this patient population. 25 , 26 …”
Section: Secukinumabmentioning
confidence: 99%
See 3 more Smart Citations
“… 23 At present, there are two anti-IL-17A biologics approved for the treatment of axSpA: secukinumab and ixekizumab. 24 Further anti-IL-17 biologics, such as brodalumab and bimekizumab, are being evaluated in clinical trials in patients with axSpA; these therapies, however, are still in clinical development and are not currently indicated in this patient population. 25 , 26 …”
Section: Secukinumabmentioning
confidence: 99%
“… 28 In 2020, secukinumab was approved for the treatment of adults with nr-axSpA with objective signs of inflammation who have responded inadequately to NSAIDs. 24 In the European Union (EU), the recommended dose of secukinumab for patients with axSpA is 150 mg by subcutaneous injection, with loading doses administered at weeks 0, 1, 2, 3 and 4, followed by subsequent doses administered every 4 weeks. 27 In contrast, in the United States (US), secukinumab 150 mg can be administered with or without the loading dose.…”
Section: Secukinumabmentioning
confidence: 99%
See 2 more Smart Citations
“…Sex differences in clinical presentation may also affect a clinician’s perception of disease severity and activity, and thus influence disease management [ 16 ]. Cytokine signalling through the interleukin-17 (IL-17) pathway is a key contributor to the pathogenesis of axSpA, and IL-17A inhibitors are an efficacious alternative to tumour necrosis factor inhibitor (TNFi) for patients with axSpA [ 17 , 18 ]. IL-17 signature studies have shown upregulated Il-17 gene expression in male patients compared to female patients [ 19 ].…”
Section: Introductionmentioning
confidence: 99%